Investigating on Effect of Salt as a Moisture Absorbent on the Performance of Moisture Energy Generator - Hossain, Md Arif; YUNOS, MUHAMAD ZAINI (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Moisture Energy Generators (MEGs) are innovative devices that can generate electricity by extracting moisture from the surrounding environment. This research aims to explore the impact of salt, which has moisture-absorbing properties, on the performance of MEGs. The study aims to design MEG films using different types of salt salt (NaCl, KCl2, ZnCl2), evaluate the influence of salt concentration on power output, and examine the physical characteristics of the MEG film. The findings indicate that salt can enhance the moisture absorption and energy conversion efficiency of MEGs. The optimal salt concentration of 10% is identified from 0% to 20% for sodium chloride, potassium chloride, and zinc chloride. The MEG film is remarkably adaptable and can extract water proficiently. This research is valuable to advancing MEGs as a dependable and eco-friendly energy source.